An architecture of virtual-live military engagement training system - YANG Xinmin, YANG Mingkai, HUANG Jingjing, GAO Qingfeng (Zhihui kongzhi yu fangzhen)
Virtual-live military engagement training can exercise the qualities and goodness to the utmost, and it is an efficient means to develop army's fighting capacity. This paper introduces the achievements of American virtual-live military engagement training system, and designs an architecture of virtual-live military engagement training system aimed at battle troops and tactical units, it binds battle and training together, and has compatibility of the virtual forces with real equipment, live exercise with simulation deduction, supports red-blue confrontation with different levels and areas. The system has six capabilities includes engagement training scenario, engagement training directing and adjusting control, engagement training arbitrament, simulation deduction, information acquisition, and engagement training evaluation. It can access not only the systems in service but also the systems in development or argument.